Selective and efficient sampling of nitrogen-containing compounds from air by in-tube extraction devices packed with zinc oxide-modified mesoporous silica microspheres - Eka Dian Pusfitasari; Cristina Youngren; Jose Ruiz-Jimenez; Saara Sirkiä; Jan-Henrik Smått; Kari Hartonen; Marja-Liisa Riekkola (Journal of Chromatography Open, 2023)
Large-sized mesoporous silica spheres loaded with different amounts of ZnO were prepared for the selective and efficient collection of nitrogen-containing compounds from air by in-tube extraction (ITEX) system. Commercial micrometer-sized chromatographic silica beads were modified using the pseudomorphic transformation approach to produce a material with narrow (2.7 nm) mesopores, while the spherical morphology of the particles was retained. The pores were infiltrated with zinc nitrate salt, which was converted to amorphous ZnO via mild thermal treatments at 300 °C. The ZnO infiltration process did not affect the morphology of the particles, but the available surface area decreased with each infiltration cycle. Sampling selectivity and efficiency were increased with the number of infiltration cycles, but problems related to the mechanical stability of the packed ITEX or backpressure were observed when the number of ZnO infiltration cycles was higher than 2. The large particle size of these materials (∼5.0 µm) decreased the backpressure on the ITEX without affecting the sampling selectivity and efficiency. Among nitrogen-containing compounds studied, sampling repeatability (n = 10) ranged between 2.4 (triethylamine) and 16.8% (isobutylamine). ITEX packing reproducibility (n = 3) ranged from 4.8 (pyridine) to 19.4% (isobutylamine). The performance of ITEX sampling devices packed with the material prepared was evaluated for targeted and untargeted analysis of nitrogen-containing compounds in air. Linear regression was used for their quantification in targeted analysis (r2 > 0.995), and the lowest LOD and LOQ values 6.6 and 21.8 ng l-1 were achieved for pyridine. Dipropylamine had the largest linear range from 23.6 to 3194.7 ng l-1. Partial least squared regression was used for the semi-quantification of the compounds identified using untargeted analysis (slope and bias equal to 1 and 0, respectively using full cross validation and Deming regression). The applicability of the ITEX systems with new sorbent materials for the analysis of nitrogen-containing compounds in indoor air, cigarette smoke and outdoor air was demonstrated. The lowest concentration was 0.7 ng l-1 for 1-nitropentane in outdoor air and the highest 1580.4 ng l-1 for acetonitrile in cigarette smoke.